2018
DOI: 10.3171/2017.5.jns162469
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-induced cardiac arrest as an alternative to temporary clipping during intracranial aneurysm surgery

Abstract: OBJECTIVE The purpose of this study was to analyze the impact of adenosine-induced cardiac arrest (AiCA) on temporary clipping (TC) and the postoperative cerebral infarction rate among patients undergoing intracranial aneurysm surgery. METHODS In this retrospective matched-cohort study, 65 patients who received adenosine for decompression of aneurysms during microsurgical clipping were identified (Group A) and randomly matched with 65 selected patients who underwent clipping but did not receive adenosine durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…The previous studies[ 2 , 5 , 9 , 11 , 13 , 18 ] have also reported relatively low incidences of transient cardiac arrhythmia and AF that resolved spontaneously and not related to the dose of adenosine. Postoperatively, elevated troponin T levels could also occur; however, it is unclear whether this finding is related to adenosine.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The previous studies[ 2 , 5 , 9 , 11 , 13 , 18 ] have also reported relatively low incidences of transient cardiac arrhythmia and AF that resolved spontaneously and not related to the dose of adenosine. Postoperatively, elevated troponin T levels could also occur; however, it is unclear whether this finding is related to adenosine.…”
Section: Discussionmentioning
confidence: 92%
“…[ 8 , 10 , 14 , 17 ] More recently, AiTA has been used as an alternative to temporary clipping in patients without IAR. [ 2 , 5 , 9 , 11 , 13 , 15 ] There are no specific indications for adenosine use, but several authors have provided expert opinion on its use, such as in a large or deep-seated aneurysms in narrow corridors where temporary clip ligation is difficult or impossible, synergy with temporary clipping, and to improve visualization of adjacent perforating arteries. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations